Characteristics of 1116 Consecutive Patients Diagnosed With Anterior Cutaneous Nerve Entrapment Syndrome (ACNES). Issue 2 (February 2021) - Mol, Frédérique M. U.; Maatman, Robbert C.; De Joode, Luuke E. G. H.; Van Eerten, Percy; Scheltinga, Marc R.; Roumen, Rudi
Abstract : Objective: The aim of this study was to discuss patient history and subjective findings at physical examination in a large case series to validate a proposed comprehensive set of major and minor diagnostic criteria. Summary Background Data: Chronic abdominal pain in some patients is caused by the anterior cutaneous nerve entrapment syndrome (ACNES). ACNES is a clinical diagnosis as no functional testing or imaging modalities are available up to date. Methods: This study retrospectively analyzed prospectively obtained data from consecutive patients who received the diagnosis ACNES during evaluation at the SolviMáx Center of Excellence for Abdominal Wall and Groin Pain, Eindhoven, The Netherlands, between June 1, 2011 and September 1, 2016. Questionnaires, standard case forms, and digital case files containing characteristics of individuals were used for analysis. Results: Data of 1116 patients suspected and treated for ACNES consistently showed the presence of the following 4 characteristics: sensory disturbances at the painful abdominal area (78%), a positive pinch sign (78%), a positive Carnett's sign (87%), and a positive response to a modified rectus sheath block (>50% pain reduction, 81%). The majority of patients are female of young or middle age with a normal BMI reporting complaints that occurred spontaneously in either a sudden or gradual timeframe, developing a severe (NRS 6-8) chronic abdominal pain that was only diagnosed after a substantial doctor's delay. Conclusion: A combination of typical findings in history and physical examination, combined with a positive modified rectus sheath block, may allow for diagnosing ACNES in patients with chronic abdominal pain. Abstract : Supplemental Digital Content is available in the text